The Experience of Marine Tribe Communities Regarding Handling Emergencies Due to Venomous Marine Animal Strings on The Coast of Bintan Regency, Riau Islands - Deliana, Muthia; Dewi Pusparianda; Putri, Rima Novia (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
The existence of Bintan Regency is surrounded by the ocean which is an ecosystem of marine animals. One of them is venomous marine animals such as constipated fish, lepu fish, jellyfish and others. Bintan Regency has a sea tribe community that lives on the coast and has its own culture in social life including treatment due to venomous marine animal stings. Handling emergencies due to venomous marine animal stings should be done with medical treatment. The results of field studies still found sea tribe communities who use traditional treatments. The purpose of this study was to explore the experiences of the sea tribe community regarding the handling of emergencies due to venomous marine animal stings on the coast of Bintan Regency, Riau Islands. The method used was a qualitative study with a phenomenological approach. Data collection was conducted with In-depth Interview. Participants were 10 marine tribesmen who had been stung by venomous marine animals. In Panglong Village, Bintan Regency, Riau Islands by purposive sampling. The research data were analyzed using the Colaizii approach. The results of this study obtained 4 themes, namely 1) seeking initial treatment with manipulative or body-based practices in reducing the effects of venomous marine animal stings, 2) biological-based practices are most commonly used in handling emergencies due to venomous marine animal stings, 3) combining beliefs with CAM practices in handling emergencies due to venomous marine animal stings, 4) overcoming ineffective treatment to medical service facilities in search of healing. The conclusion of this study is that the sea tribe community has experience using traditional medicine based on the tribe's beliefs and choosing medical treatment if the initial treatment is not effective. It is hoped that after this study, counseling can be conducted on emergency treatment due to venomous marine animal stings in collaboration with local health services